(untitled) (Journal of the College of Basic Education, 2020)
Following the developments in the film and television drama industry, as a result of the overlapping of many scientific techniques, in particular the software computer, the topics are not more than the myths or the mythical are difficult or hard to implement and the embodiment because of find and not the events and personalities The extraordinary actions of the familiar, the science and the logic, the technology, and the science were employed in the construction of the Cyclographic form, made this mediator with the ability to SIMDA, able to handle various subjects and to express the most complex of human ideas, whether philosophical, mythical or fantasy in the visual construction of the image. Like dealing with mythology has been a creative challenge since the beginnings of cinema and up to the present time, because of the intellectual richness and modernize within the myth, which means search for out-of-the-way wizards with the legend and offer it in a new form, in terms of implementation and use of digital techniques that enable the handling of the place and personality The legendary Act is an implementation level, in addition to the fact that the legend has a special character in its intellectual or philosophical depth or the fact that it is sacred when some of the nation’s scholars have realized that the legend is rooted in artistic work, as they always refer to the facts alleged to have occurred a long time ago, the essence The legend lies in the story you tell. From what the researcher outlined the problem of researching the following question: What are the The use of the legendary text in the cinematic speech?